PENGARUH PENAMBAHAN PLASTIK LDPE (LOW DENSITY POLY ETHILEN) DENGAN CARA BASAH DAN CARA KERING TERHADAP KINERJA CAMPURAN BERASPAL - Tjitjik Wasiah Suroso (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
One of method tos increase the characteristic of asphalt mixture is to add plastic in chemical term know as polymer. Generally, plastic is in pellet form so that additional equipment is needed to mix with asphalt . This equipment is not available in all regions or in Asphalt Mixing Plant Unit . Therefore, solution is required to add polymer without additional equipment. There are two kinds of mixing methods with polymer without equipment .There are two kinds of mixing methods with polymer to increase the quality of asphalt mixture i.e wet and dry process. Wet process can be performed by adding polymer into hot asphalt then mixed uniformly . Mean while, dry process can be conducted by adding polymer into hot aggregate. The purpose of the research is to compare the effects of the two mixing methods of low quality polymer (LDPE type) on asphalt mix performance with optimum asphalt content which similar to optimum asphalt content of asphalt pen 60 resulted from Marshall Test. Polymer content is 3.5% asphalt weight taken from test result of addition of polymer content variation added to asphalt (wet process). The same amount of LDPE content is also added to hot aggregate (dry process) mixed for 35 – 40 second. The laboratory result showed that the dry process has greather Marshall caracteristics, dynamic stability and Resilient Modulus greater than asphalt pen 60, but lower than wet process. Economically Dry process is cheaper because of faster mixing time, easer to handle compared to wet and no mixer required. Key words: asphalt, dry process , wet process, optimum asphalt content, polymer, characteristic of asphalt mixture.